AB0838 A Microrna Signature in Liquid Biopsies for The Diagnosis of fibromyalgia. (15th July 2016) - Iannuccelli, C.; Guzzo, M.P.; Baldassarre, A.; Di Lollo, A.C.; Masotti, A.; Valesini, G.; Di Franco, M.
Abstract : Background: Fibromyalgia (FM) is a syndrome characterized by chronic widespread pain that affects about 2–8% of the general population, especially female gender [1].The pathogenesis of FM is not completely understood and diagnosis is clinical.MicroRNAs, a class of small non-coding RNAs of ∼22–24 nucleotides, are involved in different post-transcriptional processes and have been identified as important biomarkers in many diseases [2]. Recently, it has been hypothesized that the modulation of protein expression, potentially mediated by miRNAs, is one of the main characteristic of the central and peripheral sensitization, which is a basic process to development and maintenance of chronic pain, as in FM [3]. Objectives: The aim of this study was to analyze the expression of circulating miRNAs in liquid biopsies (i.e. serum and saliva) of a group of selected FM patients. Methods: Consecutive adults FM patients, according to both ACR criteria [4, 5], and healthy donors were enrolled. Patients complaining of pain VAS more than 6 (0–10), with positivity of at least 14 tender points at clinical examination and free from drugs at the time of evaluation, were included in the study.Patients and controls completed the following questionnaires: Fibromyalgia Impact Questionnaire, Fibromyalgia Assessment Status, Health Assessment Questionnaire, Zung Self-Rating Anxiety and Depression Scale. After obtaining informed consent, samples from patients and controls were collected.Circulating miRNAs were extracted using miRCURY RNA Isolation Kit-Biofluids (Exiqon) and profiled using the Serum/Plasma Focus microRNA PCR Panel (Exiqon) following the manufacturer's instructions.Data were analyzed by SPSS software. Results: The study population consisted of 14 female patients, without diagnosis of autoimmune diseases, psychiatric or neurological disorders and neuromuscular diseases, and 14 healthy controls matched for sex and age.The exploratory profiling of circulating miRNAs in serum revealed that six miRNAs (miR-23a-3p, miR-1, miR-133a, miR-346, miR-139–5p and miR-320b) were significantly (p<0.05) and differentially regulated in FM patients compared to controls, whereas some of these miRNAs were expressed but not significantly modulated in saliva.We found a significant negative correlation (r =-0.608; p<0.05) between miR-320b and the score of depression scale.ROC curves for each miRNAs displayed a AUC greater than ∼0.7 and the best generalized linear model that can be employed to discriminate FM patients from healthy controls was obtained by taking into account only 5 miRNAs: miR-23a-3p, miR-1, miR-133a, miR-346 and miR-320b (AUC=0.954, sensitivity=100%, specificity=83.3%). Conclusions: Our preliminary work outlines the importance of using circulating miRNAs in liquid biopsies as a powerful diagnostic signature for the diagnosis of FM.Although the expression and the modulation of miRNAs seem to be site specific, we suggested a panel of serum miRNAs that can be used in the future as potential predictors of FM.A wider cohort of patients will be necessary to integrate the results that we obtained in this work and to suggest a more robust predictive model to exploit as an additional diagnostic tool for FM patients. References: Talotta et al. Clin Exp Rheumatol 2015 Andersen et al. Neurobiol Dis 2014 Gold et al. Nat Med 2010 Wolfe et al. Arthritis Rheum 1990 Wolfe et al. Arthritis Care Res 2010 Disclosure of Interest: None declared